THE IMPACT OF FISCAL DECENTRALIZATION ON CORRUPTION IN INDONESIA - , Dwi Sulihati Sri Sugiharti, Prof. Chen Kuang-hui. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Dissatisfaction and unrest in society have triggered the fall of the New Order under the Suharto Regime leading to the change of the political and budgetary system from centralized to decentralized. Decentralized systems are believed to deliver public service better through local governments under the assumption that they have better knowledge concerning the needs of the citizens in their regions as well as the available resources to be utilized for the sake of the people. Fiscal decentralization is closely related to the independency of a local government from the central government. It has become indispensable based on the reality that the local economy can no longer solely rely on the central government. Fiscal decentralization requires sustainable financial resources and local revenue source can generally be divided into two types, namely the central government transfers to local and local revenue. Although decentralization is believed to better suit the local community as it leads to better provision of public goods and service by local governments, it also shows a tendency to be imperfectly implemented due to the poor quality of the bureaucracy in some regions which are inefficient in performing their tasks. A large number of local civil servants are not recruited based on merit. Instead, they become civil servants because of their kinship and closeness to certain high-ranking officials. This condition may contribute tothe possibility of power misuse leading to corruption, as part of the patron clientelism culture in Indonesian politics. This study finds that the effect of fiscal decentralization to reduce corruption is slightly weak from the statistical point of view, while government salary and non-salary expenditures, and local election have significant negative impacts. It seems that the result is able to explain the seemingly ambiguous effect of fiscal decentralization in Indonesia.